Is climate a “risk multiplier” in Ethiopia? - Pacillo, Grazia; Achicanoy Estrella, Harold Armando; Ramírez Villegas, Julián Armando; Craparo, Sandro; Basel, Ashleigh Megan; Villa, Victor; Liebig, Theresa Ines; Schapendonk, Frans; Carneiro, Bia; Resce, Giuliano; Ruscica, Giosuè; Läderach, Peter R.D. (CGIAR FOCUS Climate Security, 2021)
Ethiopia experiences high climate variability, conflict, and political uncertainty while widespread food and nutrition insecurities are common throughout its population. CGIAR and WFP conducted a study to better understand how Ethiopia’s climate, socio-economic, and political risks and insecurities are linked to each other. This information can orient strategies and planning of long-term peacebuilding efforts and mitigate conflict risk in a climate crisis and inform strategies to strengthen the role of food for peace.